A radio-emitting outflow in the quiescent state of A0620-00: implications for modelling low-luminosity black hole binaries - Gallo, E.; Fender, R.; Miller-Jones, James; Merloni, A.; Jonker, P.; Heinz, S.; Maccarone, T.; van der Klis, M. (Wiley-Blackwell Publishing Ltd., 2006)
Deep observations with the Very Large Array of A0620–00, performed in 2005 August, resulted in the first detection of radio emission from a black hole binary at X-ray luminosities as low as 10-8.5 times the Eddington limit. The measured radio flux density, of 51 ± 7 µJy at 8.5 GHz, is the lowest reported for an X-ray binary system so far, and is interpreted in terms of partially self-absorbed synchrotron emission from outflowing plasma. Making use of the estimated outer accretion rate of A0620-00 in quiescence, we demonstrate that the outflow kinetic power must be energetically comparable to the total accretion power associated with such rate, if it was to reach the black hole with the standard radiative efficiency of 10 per cent. This favours a model for quiescence in which a radiatively inefficient outflow accounts for a sizable fraction of the missing energy, and, in turn, substantially affects the overall dynamics of the accretion flow. Simultaneous observations in the X-ray band, with Chandra, confirm the validity of a non-linear radio/X-ray correlation for hard state black hole binaries down to low quiescent luminosities, thereby contradicting some theoretical expectations. Taking the mass term into account, the A0620-00 data lie on the extrapolation of the so-called Fundamental Plane of black hole activity, which has thus been extended by more than two orders of magnitude in radio and X-ray luminosity. With the addition of the A0620-00 point, the plane relation provides an empirical proof for the scale invariance of the jet-accretion coupling in accreting black holes over the entire parameter space observable with current instrumentation.